ANALYSIS TEACHER IN STUDENTS' CREATIVE THINKING ABILITY THROUGH PROBLEM SUBMITTING - Wright Butler (Sensei International Journal of Education and Linguistic, 2023)
One of the problems in learning is the low ability of students to solve problems (story questions), especially non-routine or open-ended questions. This is due, in part, to students' weaknesses in aspects of creative thinking skills needed to solve problems. To overcome this, appropriate learning is needed, one of which is learning by proposing problems (Problem Posing). Problem posing is an activity task that leads to a critical and creative attitude. Critical thinking skills must be possessed by students in order to be able to face various personal and social problems in their lives. Critical thinking ability is the ability to think reflectively and reason in making decisions. This research is a qualitative descriptive study with the aim of describing students' abilities in constructing critical thinking. The results of this study indicate that not all aspects of creative thinking ability increase, especially flexibility in solving problems. But for the aspect of understanding problem information, novelty and fluency in answering questions has increased. Other results show that the ability to solve problems and pose problems has progressed/increased.